Assessing the Effectiveness and Feasibility of a Clinical Supervision Course Learning Module - Samsilayurni Samsilayurni; Erwan Dirgantara (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aims to develop an innovative learning module for Clinical Supervision courses that aligns with contemporary practices in educational supervision. The module is designed to support both effective learning and the application of modern pedagogical approaches. The research employed a Research and Development (RD) approach using the 4D model—Define, Design, Develop, and Disseminate. Module content and media were validated by two subject matter experts and two media design experts. A limited trial was conducted with seventh-semester students from the Educational Administration program. Validation results indicated high feasibility: 87.05% from subject matter experts and 83.33% from media experts, both falling into the "very feasible" category. Student feedback was overwhelmingly positive, with response rates exceeding 85% across all assessed aspects. The module stands out for its integration of real-world supervision cases, structured reflective assignments, and the incorporation of modern digital tools like Articulate Storyline and Canva, enhancing both visual engagement and interactivity. The findings suggest the developed module is pedagogically sound, relevant to field demands, and well-received by both experts and students. Its innovative elements offer a significant enhancement over traditional modules. While this formative research confirms the module’s viability and student acceptance, it does not assess learning outcome effectiveness. Future studies are recommended to empirically evaluate the module's impact on developing student supervision competencies.